KETERJANGKAUAN, DUKUNGAN, DAN KENDALA PELAKSANAAN PROGRAM MAGANG MANDIRI—MBKM PADA PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA FKIP UNIVERSITAS TANJUNGPURA - Ahmad Rabiul Muzammil; Mariyadi Mariyadi (Jurnal Visi Ilmu Pendidikan)
This research aims to reveal perceptions of affordability, support and obstacles to implementing the Independent-MBKM Internship Program in the Indonesian Language Education Study Program, FKIP, Untan. This research utilizes research data in the form of perceptions of students participating in the 2021-2023 Independent Internship—MBKM program, totaling 26 people regarding the affordability of the program. Research data in the form of perceptions from 7 teaching and educational staff regarding support and obstacles to implementation. The data obtained was analyzed descriptively with the help of the SPSS application. This research succeeded in revealing that students responded positively to the ease of accessing the program. This research also succeeded in revealing that teaching and educational staff have provided good support to students and believe that the Independent Internship program is able to prepare students for the world of work and increase employment opportunities. The obstacles experienced were course recognition and limited time.